2019
DOI: 10.3233/kca-180044
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy for Renal Cell Carcinoma with Inferior Vena Cava Thrombus – Initial Experience Report and Literature Review

Abstract: Background: Renal cell carcinoma (RCC) with inferior vena cava thrombus (IVC-TT) represents a relatively infrequent presentation. Curative treatment includes extirpative surgery; however, this is associated with high rates of recurrence and complications. Stereotactic body radiation therapy (SBRT) has been used to treat metastatic RCC with good results. SBRT may be used as part of multimodal therapy to provide local control of IVC-TT. Objective: We report our initial experience with SBRT to IVC-TT, including e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…However, the radiographic response rate was not adequately reported in previous neoadjuvant studies and thus remains unclear. According to our results, no significant downgrading of the IVC-TT or reversal of IVC wall invasion was observed 2–4 weeks after SABR, but the radiographic results showed a decrease in enhancement, consistent with the observations of Freifeld et al and Hannan et al, which probably resulted from local edema and vascular reduction in the IVC-TT [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the radiographic response rate was not adequately reported in previous neoadjuvant studies and thus remains unclear. According to our results, no significant downgrading of the IVC-TT or reversal of IVC wall invasion was observed 2–4 weeks after SABR, but the radiographic results showed a decrease in enhancement, consistent with the observations of Freifeld et al and Hannan et al, which probably resulted from local edema and vascular reduction in the IVC-TT [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Three studies used SABR as an alternative therapy for surgery, and only one study focused on the safety of SABR as neoadjuvant therapy. Hannan et al and Freifeld et al were the earliest reporters to use SABRs for IVC-TT and metastasis treatment, with no occurrence of severe AEs [ 17 , 18 ]. Additionally, one patient showed an excellent oncologic prognosis of 54 months.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies used SABR as an alternative therapy for surgery, and only one study focused on the safety of SABR as neoadjuvant therapy. Hannan et al and Freifeld et al were the earliest reporters to use SABR for IVC-TT and metastasis treatment, with no occurrence of severe AEs (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…And the team’s long-term follow-up results of two cases showed that SABR to RCC with IVCTT could get good local tumour control in selected patients. 19 Its safety and effectiveness need to be further examined.…”
Section: Introductionmentioning
confidence: 99%